The Ductile to Brittle Transition in Polycrystalline Ice under Compression - Schulson, Erland M. (1993)
Under monotonically increasing compressive loading, polycrystalline ice undergoes a transition from ductile to brittle behavior upon increasing the strain rate to above a critical level. Correspondingly, the dependence of the failure stress on the strain rate changes from strongly positive to weakly negative; i.e., from strain rate hardening to moderate strain rate softening. Also, upon reaching the transition, the failure stress becomes dependent upon grain size, increasing as the grain size decreases. These characteristics indicate that different deformation mechanisms operate on either side of the transition. They indicate further that the transition marks the point at which the ice reaches its highest strength. In practical terms the ductile-to brittle transition sets the maximum force a moving ice cover (e.g., on a river) exerts against an obstacle (e.g., a bridge pier). The problem therefore, is to understand the origin of this transition. To this end a systematic experimental investigation was carried out at -10 deg C on columnar, fresh-water ice. The work was guided by the hypothesis that the transition occurs when cracks, nucleated during loading, be to propagate. The hypothesis was verified.